OVEROPTIMISM AND ENTREPRENEURIAL ECOSYSTEM:CITIES OF BOGOR AND DEPOK - Arthur Tunggul Siahaan; Agus W. Soehadi; Ade Febransyah; Eko Suhartanto (Jurnal Manajemen dan Kewirausahaan, 2026)
Introducing innovative products and services by start-ups can positively influence a country’s competitiveness. The environment represented by the entrepreneurial ecosystem (EE) stimulates entrepreneurship and influences founders’ cognitive bias. Overoptimism has been studied as one of the main cognitive biases and found to be critical to new product development success (NPDS) or new venture performance (NVP). Nonetheless, studies on the EE influencing founders’ overoptimism remain limited. This study aims to fill this gap by investigating the influence on overoptimism of the two most prominent EE domains based on the World Economic Forum’s EE heatmap, namely the market and human capital domains. This study employs a questionnaire-based survey of 45 founders from digital start-ups in Bogor and Depok, Indonesia. The data is analyzed with partial least square structural equation modeling (PLS-SEM), finding that both EE domains significantly and positively influence overoptimism. In addition, the findings support previous studies by examining the influence of overoptimism on NPDS and NVP.